Association between immune-related adverse events and long-term survival outcomes in patients treated with immune checkpoint inhibitors. (June 2020) - Maillet, Denis; Corbaux, Pauline; Stelmes, Jean-Jacques; Dalle, Stéphane; Locatelli-Sanchez, Myriam; Perier-Muzet, Marie; Duruisseaux, Michaël; Kiakouama-Maleka, Lize; Freyer, Gilles; Boespflug, Amélie; Péron, Julien
Abstract: Background: The impact of immune-related adverse events (irAE) on survival outcomes after single-agent immune checkpoint inhibitors (ICIs) remains unclear. We aimed to evaluate the association between irAEs and ICI efficacy in various malignancies. Methods: All patients treated with a single-agent ICI for any advanced cancer were included in this retrospective multicentric series. The primary objective was to assess the impact of all type grade ≥II irAEs on progression-free survival (PFS) and overall survival (OS). IrAEs were first considered as a fixed covariate and included in Cox-regression models. In addition, as irAEs are time-related events and can occur at any point during follow-up, we analysed the occurrence of irAEs as a time-varying covariate. Results: In this cohort of 410 patients, the majority of patients (70%) were treated for non-small cell lung cancer. The ICI was an anti-PD(L)1 for 356 patients (82%) and an anti-CTLA4 for 79 patients (18%). In total 126 (29%) of the patients presented at least one grade ≥II irAEs. The first occurrence of a grade ≥II irAE had a positive impact on PFS and OS when considered as a fixed or as a time-varying covariate (hazard ratio [HR] for PFS = 0.63, 95% confidence interval [CI] 0.50–0.81; P = 0.00022; HR for OS = 0.57, 95% CI 0.43–0.74, P < 0.0001). This overall finding was confirmed in patients treated with an anti-PD(L)1 and among patients with lung cancer. Conclusion: In this pooled multi-institutional cohort, the incidence of irAEs was associated with better long-term survival across different malignancies treated with ICI monotherapy. Highlights: Incidence of immune-related adverse events (irAEs) has a positive impact on progression-free survival and overall survival. This overall finding was confirmed in patients treated with an anti-PD(L)1. These results were confirmed when irAEs were considered as a time-varying covariate.